The theory of wasting assets with reference to the regulation and pricing of gold in the South African gold mining industry - Boyle, Georgina Ann (School of Economics, 2023)
The main aim of this thesis is to present and critically analyse the theory of wasting assets with regard to extractive mineral industries in general and to the pricing and regulation of gold . ii'" particular. Furthermore, to consider the contention that the. price of minerals {such as gold) has been "too low11 in the current generation and that market forces have· led to a 11 too rapid11 depletion of these · resources. The argument that H is the government's duty to intervene and extend the lives of the mines is· also queried •. A detailed examination of the South African· gold mining taxation formula attempts to show how this type of· government intervention (in the for in of .a sliding scale taxation formula) results in uneconomic act ions by mine owners and non-optimal extraction patterns of the resource The contention is put forward that, given certain considerations, market ibrces should lead to the most optimal use of an exhaustible resource where property rights exist and are def inable0 Unlike common property resources, such as the fisheries, where market .forces fail to make the most optimal use of the resource, government intervention is unjustified The scope of the paper is intended to cover both the underlying theory of wasting assets and to relate this theory to gold in part icu1 ar., The determinants of the gold price will be considered as well as the effects of government intervention via· the gold mining taxation formula on the South· African gold mining industry. Hence, the thesis is divided into two sections: "Theoretical 11 and "Gold and Gold Mining". With regard to the method of paper - Literature. from as far back ,· as 1931 regarding .the theory of wasting assets, was collected and .analysed. The information for the section on 11 Gold and Gold Mining" was collected from the various organisations involved in the industry, notably the Chamber of Mines _and the Mineral Engineering Department . . 9f the University of the Witwatersrand. Information regarding the Gold Mining Taxation and Lease Formulae was obtained from the various Government Reports that have been printed since the introduction of the Mining Taxation. Act No. 6 in 1910